Sex and age significantly modulate cardiovascular disease presentation in type 2 diabetes: a large population-based cohort study - Jiménez, Amanda; Vlacho, Bogdan; Mata-Cases, Manel; Real, Jordi; Mauricio, Dídac; Franch-Nadal, Josep; Ortega, Emilio (Frontiers in Endocrinology, 2024)
Aims: We aimed to describe and compare the incidence of the first cardiovascular event and its major subtypes, coronary heart disease (CHD), cerebrovascular disease, heart failure (HF), or peripheral artery disease (PAD), according to age and sex in a population-based cohort of individuals with type 2 diabetes (T2D) from a Mediterranean region.We used linked primary care electronic medical reports, pharmacy-invoicing data, and hospital admission disease registry records from the SIDIAP database, which contains linked data for 74% of the Catalonian population. We selected individuals with T2D aged 30 to 89 years free of cardiovascular disease (CVD). The primary outcome was the first presentation of CVD.Results: The study cohort included 247,751 individuals (48.6% women, 66.8±11.9 years). During a 6.99-year follow-up, the cumulative incidence of the first cardiovascular event was 23.4%. Men were at higher risk for CVD (hazard ratio [